Institutional Problems in Regional Public Services - Aneta, Asna; Aneta, Yanti; Dama, Hais (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
The objective of this descriptive qualitative research is to explore and to analyze the institutional problems in regional public services. It employed direct observation and interview focusing on the issues of the regional public service institutions. This study was conducted at One-stop Administration system (henceforth called Samsat) in Gorontalo City. The results show that the implementation of the services is carried out according to the standard operation of the services, ranging from the procedures, work duration, service products, and innovation. Nevertheless, the problems surrounding the institution are inevitable. The issues revolve around a) the system and organization of the implementation, b) limited qualified human resources, c) lack of facilities and infrastructures, as well as d) the service strategy.